Corneal Endothelial Cell Density and Morphology After Phacoemulsification in Patients With Primary Open-Angle Glaucoma and Cataracts: 2-Year Results of a Randomized Multicenter Trial. Issue 3 (March 2019) - Ianchulev, Tsontcho; Lane, Stephen; Masis, Marisse; Lass, Jonathan H.; Benetz, Beth Ann; Menegay, Harry J.; Price, Francis W.; Lin, Shan
Abstract : Purpose: To evaluate corneal endothelial cell density (ECD) and morphology 2 years after phacoemulsification in subjects from the COMPASS trial (ClinicalTrials.gov, NCT01085357) who had mild-to-moderate primary open-angle glaucoma and visually significant cataracts. Methods: The central corneal endothelium was evaluated by serial specular microscopy at 0 to 24 months. ECD, coefficient of variation, and percentage of hexagonal cells were evaluated by a central image analysis reading center and central corneal thickness (CCT) was evaluated by ultrasound pachymetry. Results: Of 131 subjects who underwent routine phacoemulsification, analyzable endothelial images at 24 months were available for 126 subjects (96.2%). Mean ± SD central ECD at baseline was 2453 ± 359 cells/mm 2, decreasing by 10% ± 14% to 2195 ± 517 cells/mm 2 at 3 months ( P < 0.001) but stabilizing thereafter with mean endothelial cell loss (ECL) from baseline to 24 months of 9% ± 13% ( P < 0.001). Twelve (9.5%) and 10 (7.9%) subjects experienced >30% ECL at 12 and 24 months, respectively. Neither coefficient of variation nor percentage of hexagonal cells changed significantly from baseline at any time point. Mean CCT was similar at baseline (550 ± 35 μm) and at 12 months (551 ± 37 μm) and 24 months (555 ± 35 μm). Age was significantly associated with ECL after cataract surgery ( P = 0.02), but baseline intraocular pressure, number of glaucoma medications, and CCT were not. Similar results were observed in patients who underwent CyPass micro-stent implantation accompanying phacoemulsification. Conclusions: Phacoemulsification in eyes with mild-to-moderate primary open-angle glaucoma results in early ECL, with ECD stabilizing after 3 months and no effect on other endothelial stress markers up to 2 years postoperatively.